WEAPONS BASED ON NEW PHYSICAL PRINCIPLES: : DIRECTIONS FOR MODERNIZING RUSSIAN CRIMINAL LEGISLATION - Abasalieva, Elona Enverovna (International Journal of Law in Changing World, 2025)
In today’s rapidly shifting geopolitical landscape, there is growing concern about weapons based on new physical principles—technologies that remain largely unknown to the public but may pose significantly greater threats than conventional arms. These weapons can have biological effects comparable to radiation exposure, including burns and other damage to living organisms. This article highlights the urgent need to strengthen biological safety measures in the Russian Federation in response to these emerging threats. The scientific novelty lies in the author's proposal of a draft Article 222.3 for the Criminal Code of the Russian Federation, aimed at establishing legal liability for the illegal trafficking of such advanced weapons. Additionally, the author offers legislative recommendations to improve the system for recording and addressing crimes related to these technologies. By advancing legal frameworks, the study seeks to enhance protection mechanisms against a new generation of potentially devastating weaponry. _____ ARMAS BASADAS EN NUEVOS PRINCIPIOS FÍSICOS: ORIENTACIONES PARA LA MODERNIZACIÓN DE LA LEGISLACIÓN PENAL RUSA En el cambiante panorama geopolítico actual, existe una creciente preocupación por las armas basadas en nuevos principios físicos: tecnologías que, aunque siguen siendo en gran medida desconocidas para el público, pueden representar amenazas significativamente mayores que las armas convencionales. Estas armas pueden tener efectos biológicos comparables a la exposición a la radiación, incluyendo quemaduras y otros daños a los organismos vivos. Este artículo destaca la urgente necesidad de reforzar las medidas de seguridad biológica en la Federación Rusa en respuesta a estas amenazas emergentes. La novedad científica reside en la propuesta del autor de un proyecto de artículo 222.3 para el Código Penal de la Federación Rusa, cuyo objetivo es establecer la responsabilidad legal por el tráfico ilícito de estas armas avanzadas. Además, el autor ofrece recomendaciones legislativas para mejorar el sistema de registro y lucha contra los delitos relacionados con estas tecnologías. Mediante el avance de los marcos legales, el estudio busca fortalecer los mecanismos de protección contra una nueva generación de armas potencialmente devastadoras. ______ 基于新物理原理的武器：俄罗斯刑事立法现代化方向 在当今瞬息万变的地缘政治格局中，人们日益担忧基于新物理原理的武器——这些技术在很大程度上仍不为公众所知，但可能构成比常规武器更大得多的威胁。这些武器可能产生与辐射照射相当的生物效应，包括烧伤和其他对生物体的损害。本文强调，为应对这些新兴威胁，俄罗斯联邦迫切需要加强生物安全措施。其科学创新之处在于作者提出了《俄罗斯联邦刑法典》第222.3条草案，旨在确立此类先进武器非法贩运的法律责任。此外，作者还提出了立法建议，以改进与这些技术相关的犯罪记录和处理系统。该研究旨在通过推进法律框架，加强对新一代潜在毁灭性武器的防护机制。